Jewish cultural encounters in the ancient Mediterranean and Near Eastern world - Popović, Mladen.; Schoonover, Myles.; Vandenberghe, Marijn. (Supplements to the Journal for the Study of Judaism, 2017)
The essays in this volume originate from the Third Qumran Institute Symposium held at the University of Groningen, December 2013. Taking the flexible concept of "cultural encounter" as a starting point, the essays in this volume bring together a panoply of approaches to the study of various cultural interactions between the people of ancient Israel, Judea, and Palestine and people from other parts of the ancient Mediterranean and Near Eastern world. In order to study how cultural encounters shaped historical development, literary traditions, religious practice and political systems, the contributors employ a broad spectrum of theoretical positions (e.g., hybridity, métissage, frontier studies, postcolonialism, entangled histories and multilingualism), to interpret a diverse set of literary, documentary, archaeological, epigraphic, numismatic, and iconographic sources.